MODELING OF MICE AS TEST ANIMALS FOR A PRECLINICAL STUDY OF HYPOLIPIDEMIC AGENTS - Setiyo Budi Santoso; Widarika Santi Hapsari; Renny Setyowati (Universitas Muhammadiyah Magelang, 2023)
Animal models suitable for preclinical research are necessary for the discovery of hypolipidemic agents. Various publications have presented alternative dyslipidemia animal models, but identifying a feasible and stable method would serve as a solid reference for researchers. This investigation aimed to establish a sustained dyslipidemia induction that persists after several days of intervention with a hypolipidemic agent. Six groups of mice, each consisting of five primary test animals and one reserve test animal, were used. After a seven-day acclimatization period, we induced each group for 14 days using three different methods: (1) 5% body weight of quail egg yolks (5% QEY), (2) 10% body weight of used cooking oil (10% UCOs), and (3) a combination of 5% QEY and 10% UCOs. Once all mice reached their peak lipid levels, we evaluated lipid performance through a seven-day intervention with simvastatin (0.026 mg/20-gram body weight) in one of the paired groups. A 14-day combined induction of 5% QEY and 10% UCOs resulted in a 39% elevation in mouse lipids compared to baseline levels. Our findings offer an alternative to traditional dyslipidemia models. However, the development of an animal model for dyslipidemia still poses challenges. Therefore, the identification of novel biomarkers capable of targeting dyslipidemia in humans is crucial.